The awareness of pedestrian safety among Malaysians / Mohamad Afiq Danial Mohammad Fauzi, Muhamad Syafiq Jamadi and Muhammad Amin Hazal - Mohammad Fauzi, Mohamad Afiq Danial; Jamadi, Muhamad Syafiq; Hazal, Muhammad Amin (2020)
A record in Malaysia shows that road injuries have been the largest issue with up to 6000 occur in fatal accidents and over 10,000 in minor and major incident annually. By focusing on the most vulnerable road users, which is the pedestrian, an average of more than 500 accidents happen in each year that cause death. Until today, not many research have been done on this topic with comprehensive method to identify what is the main reason to effect the pedestrian safety awareness. Thus, this study attempt to identify the level of awareness for every respondent recorded and ﬁnding the most signiﬁcant factor that effects the pedestrian safety awareness. 398 sampled was selected using convenience sampling and online questionnaire is used as research instrument for this study. Ordinal logistic regression model is used in identify the signiﬁcant factors. From the study, the result shows that knowledge and behavior is the most signiﬁcant factor effecting the awareness in this study. The study shows that 39.7% total variation of the pedestrian awareness level can be explained by the independent variable while the remaining 60.3% are explained by other factor.